Avian Influenza Clade 2.3.4.4b: Global Impact and Summary Analysis of Vaccine Trials - László Kovács; Máté Farkas; Péter Ferenc Dobra; Georgia Lennon; László Péter Könyves; Miklós Rusvai (Vaccines)
Background: Avian influenza (AI), caused by orthomyxoviruses, is a globally significant disease affecting avian and non-avian species. It manifests in two variants, according to the two biovariants of the virus differentiated as highly pathogenic avian influenza (HPAI) and low pathogenic avian influenza (LPAI) strains, both of which compromise animal welfare, reduce productivity, and cause substantial economic loss. The zoonotic potential of HPAI strains, particularly the currently dominant clade 2.3.4.4b, raises concerns about public health and epidemic risks. This review assesses the results of current vaccine trials targeting HPAI clade 2.3.4.4b, emphasizing these studies because most outbreak strains in domestic poultry currently belong to this dominant clade. Methods: Multiple scientific databases comprised reports of research trials on vaccine efficacy against HPAI clade 2.3.4.4b. The Boolean term “Clade 2.3.4.4b AND vaccine” was entered into the following databases: PubMed, PubAg, Scopus, Cochrane Library, and ScienceDirect. Results: The resulting papers were analyzed. Studies revealed that antigenic similarity between vaccine and field strains enhances protective efficacy (PE), reduces viral shedding, and improves hemagglutination inhibition titers. While multivalent vaccines showed potential, results were inconsistent and varied depending on strain compatibility. Single-dose vaccines may provide sufficient PE for poultry, though ducks and geese often require multiple doses, and long-term PE is yet unknown. It was discovered that vector vaccines can provide appropriate PE against clade 2.3.4.4.b. Conclusions: Further analysis is needed as their effects may be short-lived, and subsequent doses may be required. Limited research exists on the long-term efficacy of these vaccines and their effectiveness in many avian species. Addressing these gaps is crucial for optimizing vaccination strategies. A re-evaluation of vaccination strategies is recommended but essential to implement adequate biosecurity measures on in poultry farms. This review synthesizes current evidence and may assist veterinarians and authorities in deciding whether to apply or license vaccines to reduce economic losses caused by AI.